2011
DOI: 10.1590/s1806-66902011000100025
|View full text |Cite
|
Sign up to set email alerts
|

Degradação ruminal de silagem de capim-elefante com adição de vagem de algaroba triturada

Abstract: Resumo -Esta pesquisa foi realizada visando-se avaliar a degradação ruminal da matéria seca (MS), proteína bruta (PB) e fibra em detergente neutro (FDN) de silagens de capim-elefante colhido aos 70; 90 e 110 dias após rebrota, com inclusão de 0; 5; 10 e 15% de vagem de algaroba triturada, com base na matéria natural, em delineamento inteiramente casualizado arranjado em parcelas subdivididas. Amostras de cada silagem foram incubadas no rúmen de duas vacas Jersey por 3; 6; 12; 24; 48; 72 e 96 h, sendo os saquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
2
3
1
3
Order By: Relevance
“…Even with a reduction in NDF and ADF (p < 0.05) with the addition of MPM in the diets, their contents have risen, since the MPM presents NDF and ADF associated with a higher DM intake according to the replacement. These results corroborate those reported by Batista et al (2006) and Rêgo et al (2011) which included MPM in elephant grass silage and observed a linear decrease (p < 0.05) in NDF and ADF of the experimental diets.…”
Section: Resultssupporting
confidence: 92%
“…Even with a reduction in NDF and ADF (p < 0.05) with the addition of MPM in the diets, their contents have risen, since the MPM presents NDF and ADF associated with a higher DM intake according to the replacement. These results corroborate those reported by Batista et al (2006) and Rêgo et al (2011) which included MPM in elephant grass silage and observed a linear decrease (p < 0.05) in NDF and ADF of the experimental diets.…”
Section: Resultssupporting
confidence: 92%
“…Probably, this difference, as previously discussed, are related with protein, lignin, NDIN and ADIN contents in the silages, where the highest inclusion contents might have negatively influenced the potentially soluble fraction (b) and degradation rate (c). The DM effective degradability at 0.05 h -1 rumen passage rate was lower than the observed by Rêgo et. al.…”
Section: Resultscontrasting
confidence: 73%
“…Quando os níveis de carboidratos solúveis do material ensilado são altos, as bactérias ácido- láticas serão extremamente ativas, resultando em silagens de baixo pH e com alto conteúdo de ácido lático (PIRES et al, 2009). Os efeitos da inclusão de vagens nessa pesquisa se assemelham a média de pH (3,57) obtida por Rego et al (2011) quando da inclusão de 15% de vagens de algaroba trituradas em silagens de capim elefante.…”
Section: Resultsunclassified